No Other Will Do - Witemeyer, Karen (Bloomington, Minnesota : Bethany House, a division of Baker Publishing Group, 2016)
"Men are optional. That was the credo Emma Chandler's suffragette aunts taught her and why she started a successful women's colony in Harper's Station, Texas. But when an unknown assailant tries repeatedly to drive the women out, Emma is forced to admit they might need a man after all. One who can fight. And there is only one she trusts enough to ask"--
Keywords: Suffragists -- Fiction; Man-woman relationships -- Fiction; Frontier and pioneer life -- Fiction -- Texas; Texas -- Fiction -- Social life and customs -- 19th century; Historical fiction; Romance fiction